New mechanisms in cancer metastasis : tumor-endothelial contact-induced angiogenesis and autophagy in the progression of distant metastases - Chiew, Geraldine Giap Ying (2017)
Cancer is one of the leading causes of death worldwide and is a complicated disease with many manifestations. Angiogenesis and autophagy contribute to the survivability and metastatic ability of cancer cells, thus leading to the progression of the disease. Insights on the mechanisms that drive cancer progression facilitate treatment of the disease. Therefore, this thesis focuses on tumor-endothelial contact-induced angiogenesis and the role of autophagy in the progression of distant metastases, in order to develop therapeutic strategies to halt cancer progression. I developed a two-dimensional (2D) liver cancer-endothelium co-culture model wherein endothelial cells in direct contact with liver cancer cells were able to differentiate and form tubular structures similar to those plated on matrigel. Growth factors were not the key inducers of angiogenesis, and contact dependent differentiation of endothelial cells were indispensable in the co-culture model. Further investigation of the angiogenic programming mechanism in the co-culture revealed that inhibitors of FAK and Ras/Raf/MEK/ERK pathways effectively inhibited the differentiation of endothelial cells, while the VEGFR inhibitor displayed little effect. Taken together, this co-culture model was able to provide insights on the tumor-endothelium interactions in the differentiation and remodeling of endothelial cells. In order to increase the relevance of the previous study and to develop a potential platform for the discovery of new anti-angiogenic/anti-tumor agents for liver cancer therapy, I further developed the 2D co-culture model into a three-dimensional (3D) co-culture tumor spheroidal model. Addition of factors and inhibitors, which targets the cellular signaling pathway, to the model system allowed better understanding of mechanisms regulating hepatocellular carcinoma (HCC) development. The 3D model demonstrated similar protein expressions to a HCC xenograft model, and exhibited upregulation of signaling proteins in the 3D model compared to the 2D model. The effects of several anti-angiogenic agents like sorafenib, sunitinib, and axitinib were analyzed in the 3D co-culture model by utilizing fluorescent proteins, and a FRET-based caspase-3 sensor in the endothelial cell, which can detect apoptosis in real time, allowing for dual multi-screening of anti-angiogenesis and anti-tumor drugs in one-step. Finally, the autophagic capabilities of lung metastases-derived cell lines that were isolated from mice models were also studied in this thesis. The metastases-derived breast cancer cells experienced increased basal levels of autophagy and underwent stronger autophagy during serum deprivation compared to the parental breast cancer cell line. The metastases-derived cells formed large autophagic vacuoles during serum deprivation and these autophagic vacuoles were discovered to contain autophagic cargo. Inhibition of autophagic flux enhanced the vacuoles, while inhibition to formation of autophagosomes reduced the vacuoles. Furthermore, the formation of the autophagic vacuoles was found to be inhibited by antioxidant and analysis of the parental and metastases-derived cells revealed differences in their antioxidant capabilities. This contributes to increasing evidences of enhanced autophagy capabilities in cancer progression and metastasis, and provides an insight to the role of antioxidant capabilities in regulating autophagy in cancer cells. Overall, I studied two important aspects in cancer metastasis: angiogenesis and autophagy. I have revealed new insights into contact-dependent cancer angiogenesis and provided evidences of differential autophagic capabilities linked to antioxidant defenses mechanism in cancer metastasis. Discovering unexplored ideologies in these hallmarks may unfold new therapeutic targets in the treatment of cancer.